“Caracterización morfoagronómica de materiales promisorios de papaya(carica papaya l.) de la provincia de Manabí”. - Moreira Vera, Rubén Antonio (2015)
This research is linked to the descriptive phase of macro institutional research entitled "Response of Native Germplasm of papaya, of the ringspot virus in Manabi"; this phase was conducted from September 2013 to May 2014 in the experimental field of the Polytechnic School of Manabi Manuel Felix Lopez (ESPAM MFL), with the purpose of describing morphological and agronomic characteristics using native materials of papaya (Carica papaya) from the province of Manabi. The materials tested were 22, coming from every corner of the province. Each material was distributed in a row of 15 plants in a plot of 6210 m2. The evaluated variables were established according to the descriptors for papaya IBPGR (1988). In the morphological characterization great variability of plants and fruits were determined in size, color, and shape; as well as the organoleptic characteristics of the mature fruit. Concerning the agronomic hand, materials with higher fruit yield per harvest were PM-01-CH (Chone), and PM-16PE (PEDERNALES) and highlighted the same material PM-18 to 24-MAY (24 MAY) and PM-11-PO (PORTOVIEJO) in fruit weight because these showed the highest average regarding diameter and length.